Characterization of a wollastonite glass-ceramic material prepared using sugar cane bagasse ash (SCBA) as one of the raw materials - Teixeira, Silvio Rainho [UNESP]; Souza, Agda E. [UNESP]; Carvalho, Claudio L. [UNESP]; Reynoso, Victor C. S. [UNESP]; Romero, Maximina; Ma Rincon, Jesus (Elsevier B.V., 2014)
Glass-ceramic material prepared with sugar cane bagasse ash as one of the raw materials was characterized to determine some important properties for its application as a coating material. X-ray diffraction patterns showed that wollastonite-2M (CaSiO3) was the major glass-ceramic phase.The Rietveld method was used to quantify the crystalline (60 wt.%) and vitreous (40 wt.%) phases in the glass-ceramic. The microstructure (determined by scanning electron microscopy) of this material had a marble appearance, showing a microporous network of elongated crystals with some areas with dendritic, feather-like ordering. Microhardness data gave a mean hardness value of 564.4 HV (Vickers-hardness), and light microscopy disclosed a greenish brown colored material with a vitreous luster. (C) 2014 Elsevier Inc. All rights reserved.
Keywords: Glass-ceramics; Wollastonite; Sugarcane; Ash; Hardness; X-ray diffraction